Caribbean Report 13-07-1995 - Richards, Ken (anchor); Compton, John (interviewee); Ford, Henry (interviewee); Fraser, Tony (correspondent); Sobion, Keith (interviewee); Ghany, Hamid (interviewee); Panday, Basdeo (interviewee); Norton, Michael (correspondent); Ross, Leone (correspondent) (The British Broadcasting Corporation, 1995)
In this report: St. Lucia's Prime Minister John Compton testified before the commission of inquiry into the alleged misuse of UN funds. Under cross examination by Counsel for the Cabinet Henry Ford, Mr. Compton disputed testimony given by former UN Ambassador Dr. Charles Flemming. In Trinidad, constitutional expert Dr. Hamid Ghany warns that the country is at a constitutional precipice after the Speaker of the House threw out government's no confidence motion. In Haiti, a self-styled communist folk singer, Manno Charlemagne is to become the new Mayor of the capital Port-au-Prince. In Britain, a British- Asian man is having a legal tussle with his wife over eighteen million pounds he won in the national lottery. Steve Dean was named Man of the Match as the West Indies cricket team crashed to defeat in the fifty-five overs match against the Minor Counties in Reading.
1. Headlines with Ken Richards (00:00-00:14)
2. St. Lucia's Prime Minister testifies before the commission of inquiry (00:15-05:29)
3. A constitutional expert warns that Trinidad and Tobago is at a constitutional precipice (05:30-09:27)
4. A self-styled communist folk singer is to become the new Mayor of Port-au-Prince (09:28-12:17)
Keywords: Governmental investigations -- Saint Lucia; Political corruption -- Saint Lucia; Saint Lucia -- Politics and government; Parliamentary practice -- Trinidad and Tobago; Legislative bodies -- Trinidad and Tobago -- Presiding officers; Constitutional law -- Trinidad and Tobago; Trinidad and Tobago -- Politics and government; Mayors -- Haiti; Political leadership -- Haiti; Haiti -- Politics and government -- 1986-; Lotteries -- Psychological aspects; Lottery winners -- Great Britain; Interpersonal relations; Cricket -- West Indies; Cricket matches -- England